Photocatalytic bacterial inactivation by TiO(2)-coated surfaces - Bonetta, Silvia (Springer, 2013)
The aim of this study was the evaluation of the photoactivated antibacterial activity of titanium dioxide (TiO(2))-coated surfaces. Bacterial inactivation was evaluated using TiO(2)-coated Petri dishes. The experimental conditions optimized with Petri dishes were used to test the antibacterial effect of TiO(2)-coated ceramic tiles. The best antibacterial effect with Petri dishes was observed at 180, 60, 30 and 20 min of exposure for Escherichia coli, Staphylococcus aureus, Pseudomonas putida and Listeria innocua, respectively. The ceramic tiles demonstrated a photoactivated bactericidal effect at the same exposure time. In general, no differences were observed between the antibacterial effect obtained with Petri dishes and tiles. However, the photochemical activity of Petri dishes was greater than the activity of the tiles. Results obtained indicates that the TiO(2)-coated surfaces showed a photoactivated bactericidal effect with all bacteria tested highlighting that the titania could be used in the ceramic and building industry for the production of coated surfaces to be placed in microbiologically sensitive environments, such as the hospital and food industry.